Social inequalities in exposure to heat stress and related adaptive capacity: a systematic review - S Claire Slesinski; Franziska Matthies-Wiesler; Susanne Breitner-Busch; Geronimo Gussmann; Alexandra Schneider (Environmental Research Letters, 2025)
Extreme heat is an important public health concern, and heat stress exposure and related adaptive capacity are not equally distributed across social groups. We conducted a systematic review to answer the question: What is the effect of social disadvantage on exposure to subjective and objective heat stress and related adaptive capacity to prevent or reduce exposure to heat stress in the general population? We systematically searched for peer-reviewed journal articles that assessed differences in heat stress exposure and related adaptive capacity by social factors that were published between 2005 and 2024. One author screened all records and extracted data; a second author screened and extracted 10% for validation. Synthesis included the identification and description of specific social groups unequally exposed to heat stress and with lower adaptive capacity. We assessed European studies for the potential risk of bias in their assessment. We identified 123 relevant publications. Subjective heat stress appeared in 18.7% of articles, objective heat stress in 54.5%, and adaptive capacity in 54.5%. Nearly half came from North America (47.2%), 22.8% from Asia, and 17.1% from Europe. Publishing increased from zero articles in 2005 to 21 in 2023. Most studies considered socioeconomic status (SES) (78.8%), and many considered age (50.4%), race/ethnicity (42.3%), and sex/gender (30.1%). The identified studies show that lower-SES populations, young people, immigrants, unemployed people, those working in outdoor and manual occupations, and racial/ethnic minorities are generally more exposed to heat stress and have lower adaptive capacity. Most studies of objective heat stress use inadequate measures which are not representative of experienced temperatures. European studies generally have a low or moderate risk of bias in their assessments. Social inequalities in heat stress exposure and related adaptive capacity have been documented globally. In general, socially disadvantaged populations are more exposed to heat stress and have lower adaptive capacity. These social inequalities are context-dependent, dynamic, multi-dimensional, and intersectional. It is essential to consider social inequalities during heat-health action planning and when developing and implementing climate change adaptation policies and interventions.